ระบบสนับสนุนการตัดสินใจสำหรับงานซ่อมบำรุงไฟฟ้าแสงสว่างและไฟสัญญาณจราจรโดยใช้การให้เหตุผลตามกรณี - ปิยะพร เป็งนำสุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study titled “Decision Support System for Street Lights and Traffic Signal Maintenance Using Case-based Reasoning” aimed at solving problems, as well as developing and improving for The Machine-Vehicle maintenance Unit, is responsible for maintaining the lighting equipment and traffic equipment in the form of web application. The system will suggest the equipment which will be used to maintain the broken equipment that will increase the overall performance of work. In this research, the system consisted of modules used for Decision Support System for Street Lights and Traffic Signal Maintenance Using Case-based Reasoning such as a User management, Route management, Case-based management, Input Form Data and Notification email, Reports Management, Map Management. The system creates online form and sends email notifications when manager submit, after that the notification status form will alert to email in real-time. Also, it can provide the equipment in area on route. The system used the cases which are analyzed by the experts to be the based case for the new maintenance request in order to use less time, and create a new case-base system. Furthermore, it can show the map of system. Finally, the system provides a summary report that can be performed to complete the forms and export a report in Excel format. The results from evaluating users found that it was good on average. The system is developed in order to help the officer to get the accurate as decided by the expert answer 80%. Moreover, the use of less time will increase the overall performance of work. The system can help support the Machine-Vehicle maintenance Unit.